IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN SIKAP WIRAUSAHA BERBASIS KEARIFAN LOKAL SISWA PADA MATERI EKOLOGI KELAS X - Indrawati, Sari; Wahidin, Wahidin; Nur, Sofyan Hasanuddin (Edubiologica, 2022)
The background of this research is the low value of mastery of the concept of biology lessons in Ecology material at SMAN 1 Lohbener, due to the lack of application of a learning model that activates students in the learning process. The Project Based Learning model is a project-based learning model with one of its characteristics being product-oriented that has entrepreneurial value. The purpose of this study is to determine the improvement of students' mastery of entrepreneurial concepts and attitudes based on local wisdom. The research method used was quasi-experimental with a pretest-posttest control group design with the sample used being taken purposively as many as 50 students, which were divided into experimental and control groups. The data collection technique uses a concept mastery test, an entrepreneurial attitude questionnaire, and a student response questionnaire. The result of this study is that there is an increase in students' mastery of concepts in Ecology material through the application of a project-based learning model which is evidenced by a significant difference in mastery of the concept of the experimental class with a control class with a probability value (p) of 0.001< 0.05, and a nominal gain index of the experimental class of 0.34 with an increase in the medium category and an increase in students' entrepreneurial attitudes based on local wisdom as evidenced by the value of The normalized gain index in the experimental class was 0.03 with a low improvement category.